Patients Reporting on Appointment Date After Access Opening For Further Treatment to Dental Hospital - A Cross Sectional Study - KrishnaKanth Jaju1 , Iffat Nasim2 , J.Mahalakshmi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Failure to keep dental appointments is one of the problems affecting the outcome of treatment. Keepingdental appointments enhances patient care while failure to keep appointments can result in poor prognosis,economic cost and patient care disruption.The aim of the present study was to evaluate the number ofpatients reporting on appointment date after access opening for further treatment to dental hospital. 4490 metinclusion criteria, only 981 patients reported on the given appointment date. Data was tabulated into excelsheets. Then data was analyzed using SPSS software(23.0 version). Statistical analysis of the material wasperformed using Chi square test. Number of patients reported to the hospital on the appointment date wereonly 27.3% (1225) patients, 72.7% (3265) of patients did not report back on the given appointment date. Inthe present study 1225 patients reported for further treatment, 488 patients of 18-30 age group reported backfor further treatment, more number of male patients(665) reported back for further treatment, more numberof patients (132) with complaints in relation to 36,46 reported back for further treatment.Failure to keepdental appointments was high in the present study. Being busy with other activities and long distance weresome reasons for failed appointments.